Cognitive-Environmental Analysis of the Impact of High-Rise Construction on the Social Status of Citizens in Sari - Seyed Hassan Rasouli; Abbas Alipour Nakhi; Mohammad Ebrahimi Saraei; Mohammad Reza Gholami Pouya (اکولوژی انسانی, 2024)
This research aims to examine the cognitive-environmental perception of the impact of high-rise construction on the social status of citizens in Sari. To this end, a questionnaire has been designed containing several questions regarding demographic, social, and cultural characteristics of household heads, as well as physical housing characteristics. Additionally, it includes several items to assess respondents' satisfaction with apartment living, the extent and nature of neighborhood relationships, and the impact of apartment living on these relationships. It also addresses social, cultural, and legal issues arising from apartment living. For this purpose, 200 apartment-dwelling household heads were asked to evaluate these aspects using a Likert scale. The analysis of the collected data was conducted using SPSS software through both descriptive and analytical methods. The descriptive results obtained from this research indicate that the individual characteristics of residents significantly influence their satisfaction with apartment living. Furthermore, according to the findings, the reduction in neighborhood relationships due to apartment living has been analyzed by separating each of the individual and contextual variables, describing the relationships between the variables in question. In the inferential analysis, the Chi-square test was used to analyze the relationships between individual and contextual variables affecting satisfaction with apartment living and the decline in neighborhood relationships as a result of apartment living. The results indicated that all tests were significant across all analyses.